The Politics Of Industrial Psychology - Hayes, Grahame (PINS-Psychology in Society, 2025)
The political history of south Africa is full of many years of difficult struggles, major democratic setbacks, and occasionally some significant victories against the apartheid state and capital. It would be difficult in view of this to single out one year which was 'worse' than any of the others. However, in the event of any prizes for the hall of horrors which is our political history, 1996 should feature very prominent. 1986 saw the 'removal' of the state of emergency, only to have it reinstated with more vigour and commitment in June, just prior to what the state saw as a major potential popular mobilisation around the 10th anniversary of the 16 June student uprising of 1976. The farce of democracy was carried even further in December when wide-ranging press clamps were introduced. The state is not well, and during 1986 used a massive security force deployment in the townships and black communities in an attempt to contain any further deterioration of its ailing legitimacy. The state's legitimacy has been threatened and challenged in most areas which it administers: education; housing; security; welfare; health; industrial relations.